2020
DOI: 10.1111/1750-3841.15426
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different extraction techniques on recovery, purity, antioxidant activities, and microstructure of flaxseed gum

Abstract: Four extraction techniques (that is, hot water extraction [HWE], alkaline-acidic extraction [AAE], ultrasound assisted extraction [UAE], and microwave assisted extraction [MAE]) were compared for flaxseed gum extraction and their influence on the yield, purity, structural characterization (monosaccharide composition, molecular weight distribution, and microstructure by transmission electron microscope), and antioxidant activity (in terms of scavenging ability of 2,2diphenyl-1-picrylhydrazyl [DPPH], 2,2'-azino-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
(118 reference statements)
1
14
0
Order By: Relevance
“…In addition to the functional properties, FG also shows several biological activities. FG possesses strong antioxidant activity, which has been confirmed in several studies [ 24 , 29 , 30 , 31 , 66 ]. The antioxidant activity of FG is significantly affected by the presence of some phenolic compounds easily extractable with FG, such as caffeic acid, p-coumaric acid, epicatechin, ellagic, cinnamic, and vanillic acids.…”
Section: Flaxseed Gummentioning
confidence: 55%
See 2 more Smart Citations
“…In addition to the functional properties, FG also shows several biological activities. FG possesses strong antioxidant activity, which has been confirmed in several studies [ 24 , 29 , 30 , 31 , 66 ]. The antioxidant activity of FG is significantly affected by the presence of some phenolic compounds easily extractable with FG, such as caffeic acid, p-coumaric acid, epicatechin, ellagic, cinnamic, and vanillic acids.…”
Section: Flaxseed Gummentioning
confidence: 55%
“…Polysaccharides are easily extractable from flaxseed; it is possible to obtain them from whole seeds [ 41 ], seed hulls [ 43 ], or oilseed cake [ 27 ]. Safdar et al [ 30 ] used four methods for the extraction of FG from whole flaxseeds with differences in the relative yield of FG from flaxseeds: hot water extraction (9.0%), ultrasound-assisted extraction (7.8%), microwave-assisted extraction (7.0%) and alkaline–acidic extraction (6.4%). For the highest yield of FG, hot water extraction is preferable, whereas, for maximal purity, it is most suitable the ultrasound-assisted extraction method.…”
Section: Flaxseed Gummentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a significant reduction in the water absorption capacity and emulsifying activity index of FG has been observed with increased extraction temperature. In another study, hot-water extraction (HWE) was shown to be more advantageous than others (ultrasound-assisted extraction (UAE), alkaline–acidic extraction (AAE), and microwave-assisted extraction (MAE)) to improve the extraction yield of FG [ 20 ].…”
Section: Extraction Of Mucilagementioning
confidence: 99%
“…The ultrasonic treatment exerted a limited impact on monosaccharide composition and protein content. Safdar et al [ 20 ] showed that UAE was favorable to the purity of FG. UAE-FG showed a significantly higher scavenging ability in terms of 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) free radicals, 2,2′-diphenyl-1-picrylhydrazyl (DPPH) free radicals, reducing power, and the β-carotene bleaching assay than HWE-FG, MAE-FG, and AAE-FG.…”
Section: Extraction Of Mucilagementioning
confidence: 99%